2020
DOI: 10.1097/inf.0000000000002916
|View full text |Cite
|
Sign up to set email alerts
|

A Multicentered Study of the Clinical and Molecular Epidemiology of TEM- and SHV-type Extended-Spectrum Beta-Lactamase Producing Enterobacterales Infections in Children

Abstract: Background: Extended-spectrum β-lactamase (ESBL)-producing Enterobacterales-(Ent) infections are increasing in pediatrics. Before CTX-M ESBL emerged, the most common infection-associated ESBL genes were TEM and SHV-type ESBLs. We sought to define the current epidemiology of Ent infections in children due to bla TEM and bla SHV (TEM-SHV-Ent). Methods: A retrospective case-control analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…However, we found that among children, the mechanisms of both β-lactam and FQR are diverse, and there is significant horizontal gene transfer occurring among the Enterobacterales genera ( Logan et al., 2016 ; Logan et al., 2019a ; Logan et al., 2019b ; Logan et al., 2019c ; Logan et al., 2020a ). Over 25% of isolates phenotypically susceptible to fluoroquinolones harbored an FQR gene.…”
Section: Discussionmentioning
confidence: 95%
“…However, we found that among children, the mechanisms of both β-lactam and FQR are diverse, and there is significant horizontal gene transfer occurring among the Enterobacterales genera ( Logan et al., 2016 ; Logan et al., 2019a ; Logan et al., 2019b ; Logan et al., 2019c ; Logan et al., 2020a ). Over 25% of isolates phenotypically susceptible to fluoroquinolones harbored an FQR gene.…”
Section: Discussionmentioning
confidence: 95%
“…ESBL enzymes confer resistance to multiple antibiotics including penicillin, monobactams, and cephalosporins, commonly used to treat infections caused by Gram negative bacteria (9). There are multiple classes of ESBL enzymes including TEM, SHV, OXA and CTX-M (10)(11)(12). Recently, attention has been drawn to the CTX-M class ESBLs as it is currently the most common ESBL found worldwide (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%